Functional capacity and rehabilitation strategies in Covid-19 patients: current knowledge and challenges - Aline Xavier Frota; Marcelo Carvalho Vieira; Carla Cristiane Santos Soares; Paula Simplício da Silva; Gilberto Marcelo Sperandio da Silva; Fernanda de Souza Nogueira Sardinha Mendes; Flavia Mazzoli-Rocha; Henrique Horta Veloso; Ananda Dutra da Costa; Cristiane da Cruz Lamas; Claudia Maria Valete-Rosalino; Tatiana Rehder Gonçalves; et al. (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract Covid-19 is a novel infectious disease whose spectrum of presentation ranges from absence of symptoms to widespread interstitial pneumonia associated with severe acute respiratory syndrome (SARS), leading to significant mortality. Given the systemic pattern of Covid-19, there are many factors that can influence patient's functional capacity after acute infection and the identification of such factors can contribute to the development of specific rehabilitation strategies. Pulmonary impairment is the primary cause of hospitalization due to Covid-19, and can progress to SARS as well as increase length of hospitalization. Moreover, cardiac involvement is observed in approximately 30% of hospitalized patients, with an increased risk of acute myocarditis, myocardial injury, and heart failure, which may compromise functional capacity in the long-term. Thromboembolic complications have also been reported in some patients with Covid-19 and are associated with a poor prognosis. Musculoskeletal complications may result from long periods of hospitalization and immobility, and can include fatigue, muscle weakness and polyneuropathy. Studies that address the functional capacity of patients after Covid-19 infection are still scarce. However, based on knowledge from the multiple systemic complications associated with Covid-19, it is reasonable to suggest that most patients, especially those who underwent prolonged hospitalization, will need a multiprofessional rehabilitation program. Further studies are needed to evaluate the functional impact and the rehabilitation strategies for patients affected by Covid-19.